POSTĘPOWANIE W SPRAWIE O ROZGRANICZENIE (ZAGADNIENIA WYBRANE) - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2017)
Immovables’ Delimitation Procedure (Chosen Problems) Summary The aim of the article is to clear some doubts concerning the immovables’ delimitation procedure. The procedure takes place at the administrative body and then – if it becomes necessary – before the court which examines the case during voluntary jurisdiction proceedings. The legislator has made the possibility of a judicial way in the immovables’ delimitation procedurę dependent on some formal premises concerning the termination of the administrative proceedings. The court is only bound by the ‘objective’ extent of the delimitation procedure. It is by no means bound by the settlements accepted during the administrative procedure. It doesn’t evaluate the administrative procedure from the point of view of its legal accuracy either. The immovables’ delimitation procedure may only regard a part of a boundary between the immovables. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />